Application Of Structural Econometrics Model In The Health Care System To Describe Relationships Among Variables In The System. - Abdul Rahman, Rosmanjawati; Kamil, Anton Abdulbasah (2005)
In this paper we applied structural econometrics model into the health care system to show the interdependence between variables and to describe the relationships among them.